Analisis Watak Yang Terkandung Dalam Novel “Merindu Baginda Nabi” Karya Habiburahman El Shirazy - Katharina Woli Namang; Rabita Isnanda (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this research is to describe the personality of kholeris, melakholis, phlegmati, and sanuinis in the main character in the novel Merindu Baginda Nabi by Habiburahman El Shirazy. The research method used in this research is descriptive qualitative data analysis. The data source used in this research is the novel Merindu Baginda Nabi Karya Habiburahman El Shirazy and relevant theoretical books related to literary psychology. While the research data in this study are excerpts of sentences contained in the novel Merindu Baginda Nabi. the instrument used is a documentation guide. Then the data analysis techniques in this study are, reading carefully the contents of the novel, noting and underlining character characters, analyzing data, describing data, and drawing conclusions. From the analysis, it can be concluded that in the novel Merindu Baginda Nabi there is a personality structure that focuses on tolerant, melancholic, phlegmatic, and sanuinis in the main character named Rifa. The personality in Rifa's character is more in the personality structure of kholeris and sanguinis.